EXPERIENTIAL LEARNING IN INTRODUCING IFRS AT UNIVERSITIES IN INDONESIA - Istiningrum, Andian Ari (Jurnal Economia, 2012)
Abstract: Experiential Learning in Introducing IFRS at Universities in Indonesia. The purpose of this study is to find the appropriate learning model for accounting learning process at universities in Indonesia due to the process of convergence to IFRS that has already occurred in Indonesia. The study is conducted by reviewing, analyzing and evaluating the effects and solutions of convergence to IFRS in other countries that have already implemented IFRS. All possible accounting learning method offered by accounting lecturers in other countries are evaluated in order to find the solution that is appropriate with condition faced by Indonesian universities. The results are as follow: (i) convergence to IFRS requires that accounting learning process should underline the use of more principle-base standard, professional judgment, fair value measurement and collaboration with other professions. (ii) experiential learning through case study can be used to generate knowledge and skills of IFRS. Keywords: IFRS, accounting learning process, experiential learning, case study Abstrak:  Experiential Learning untuk Mengenalkan IFRS di Universitas-universitas di Indonesia. Tujuan dari kajian ini adalah untuk menemukan solusi dari permasalahan terkait dengan pembelajaran akuntansi berbasis IFRS dan mengevaluasi beberapa solusi yang bisa digunakan untuk mengintegrasikan IFRS dalam kurikulum akuntansi di perguruan tinggi Indonesia. Studi ini dilaksanakan dengan melakukan reviu, analisis dan evaluasi terhadap model pembelajaran akuntansi berbasis IFRS pada negara lain yang terlebih dahulu telah mengimplementasikan IFRS. Berbagai model pembelajaran dari negara lain akan dievaluasi sehingga ditemukan model pembelajaran akuntansi yang paling tepat untuk digunakan dalam pembelajaran IFRS di Indonesia. Studi ini memberikan hasil sebagai berikut: (i) Konvergensi IFRS menimbulkan perubahan pembelajaran akuntansi di mana pembelajaran harus memfokuskan diri pada penggunaan standar berbasis prinsip, pertimbangan professional, pengukuran nilai wajar, dan kolaborasi dengan bidang ilmu lain, (ii) studi kasus bisa digunakan sebagai metode pembelajaran akuntansi berbasis IFRS karena dengan studi kasus mahasiswa bisa mendapatkan pengalaman untuk melakukan konvergensi laporan keuangan dari basis US GAAP ke basis IFRS. Kata Kunci: IFRS, proses pembelajaran akuntansi, pengalaman belajar, studi kasus